2005
DOI: 10.1515/bc.2005.088
|View full text |Cite
|
Sign up to set email alerts
|

Efficient production of native actin upon translation in a bacterial lysate supplemented with the eukaryotic chaperonin TRiC

Abstract: Recombinant expression of actin in bacteria results in non-native species that aggregate into inclusion bodies. Actin is a folding substrate of TRiC, the chaperonin of the eukaryotic cytosol. By employing bacterial in vitro translation lysates supplemented with purified chaperones, we have found that TRiC is the only eukaryotic chaperone necessary for correct folding of newly translated actin. The actin thus produced binds deoxyribonuclease I and polymerizes into filaments, hallmarks of its native state. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…This theory is further supported by the work of Stemp et al (2005) and Pappenberger et al (2006) who both show that a stablefolding intermediate of actin formed in an Escherichia coli lysate in vitro translation system can reach its native form when in the presence of CCT. Furthermore, it is shown that CCT is necessary for the correct folding of newly synthesized actin and that the GroEL system cannot replace this activity (Stemp et al 2005).…”
Section: Actin and Tubulinmentioning
confidence: 73%
“…This theory is further supported by the work of Stemp et al (2005) and Pappenberger et al (2006) who both show that a stablefolding intermediate of actin formed in an Escherichia coli lysate in vitro translation system can reach its native form when in the presence of CCT. Furthermore, it is shown that CCT is necessary for the correct folding of newly synthesized actin and that the GroEL system cannot replace this activity (Stemp et al 2005).…”
Section: Actin and Tubulinmentioning
confidence: 73%
“…It is important to recognize that the production of soluble protein does not always guarantee monomericity or bioactivity of the target protein (Stemp et al, 2005;Yee et al, 2001). To determine the monomericity of the His-MBP-hBD28 fusion protein, the sonicated cell lysates were purified to remove host contaminants and loaded into a SEC column for soluble aggregate analysis.…”
Section: His-mbp-hbd28 Purification and Soluble Aggregate Analysismentioning
confidence: 99%
“…The E. coli extract is a total cleared cell lysate and thus contains bacterial chaperones such as GroEL/ES or DnaK/DnaJ/ GrpE, and some of these components may assist the prefolding of nascent actin chains and/or stabilise the Ac I intermediate once it is partially folded. 42 For example, although the Ac I chains migrate discretely on native gels, they are highly prone to aggregation; heating them to 46°C for a few minutes elicits complete aggregation compared to native actin, which is very much more stable ( Figure 6(a) and (b)). It will now be possible to ask whether any bacterial chaperones are able to enhance Ac I stability by preventing aggregation and whether any can increase native actin yield in the pure yeast CCT system.…”
Section: Testing the Site-specific Model Of Cct-actin Interactionmentioning
confidence: 99%